(untitled) (Международный научный журнал «Инженер», 2026)
The article examines the deformation joints of bridge structures that overlap gaps between span structures and other parts of the bridge (supports, supports) to ensure smooth and safe traffic flow, designed to compensate for deformations caused by temperature changes, dynamic loads, and other factors. Also, the types of stresses on deformation joints, determining the calculated temperature range, and determining the displacements of the ends of span structures from various types of stresses are described. Recommendations for choosing a deformation seam are given depending on the calculated values of displacements of the ends of the span structures. The article also examines determining the installation size of the deformation seam.